The Influence Of Work Environment And Work Discipline On Employee Performance Public Works And Spatial Planning Office Tasikmalaya City - Nirwana, Genta Abdillah; Rahwana, Kusuma Agdhi; Risana, Dudu (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this study was to determine and analyze the effect of work environment and work discipline on employee performance in civil servants at the Tasikmalaya City Public Works and Spatial Planning Office. The research method used is survey method, data obtained directly through questionnaires to 83 respondents taken from civil servants. Sample withdrawal using saturated sampling and the analysis used in this study is multiple regression analysis. Based on the results of the study, it is known that the work environment and work discipline have a positive and significant effect on the performance of employees of the Tasikmalaya City Public Works and Spatial Planning Office simultaneously. While partially, the work environment shows a positive value and significant effect, and for work discipline shows a positive value but has no significant effect.